Seismic Stability of Subsea Tunnels Subjected to Seepage - Xuansheng Cheng; Yi Ren; Xiuli Du; Yida Zhang (The Scientific World Journal)
Strength reduction method and ADINA software are adopted to study the stability of submarine tunnel structures subjected to seepage and earthquake under different seawater depths and overlying rock strata thicknesses. First, the excess pore water pressure in the rock mass is eliminated through consolidation calculation. Second, dynamic time-history analysis is performed by inputting the seismic wave to obtain the maximum horizontal displacement at the model top. Finally, static analysis is conducted by inputting the gravity and the lateral border node horizontal displacement when the horizontal displacement is the largest on the top border. The safety factor of a subsea tunnel structure subjected to seepage and earthquake is obtained by continuously reducing the shear strength parameters until the calculation is not convergent. The results show that the plastic zone initially appears at a small scope on the arch feet close to the lining structure and at both sides of the vault. Moreover, the safety factor decreases with increasing seawater depth and overlying rock strata thickness. With increasing seawater depth and overlying rock strata thickness, maximum main stress, effective stress, and maximum displacement increase, whereas displacement amplitude slightly decreases.